Investigation of Crystallite Size, Strain Effect, Initial Permeability and Optical Properties of Al Substituted Ni-Cd Dense Ferrites - Mohammed, Nur; Bagum, Arjumanara; Hossen, M Belal (Journal of Engineering Science, 2025)
Employing solution combustion technique, Al substituted Ni-Cd nanoparticles were used to prepare bulk specimen, which has the general formula Ni0.65Cd0.35Fe2-xAlxO4 (x=0, 0.015, 0.030, 0.045, 0.060) and demonstrates how the amount of Al substitution tunes the crystallite size effect, strain effect, permeability and optical properties of the compounds. Crystallite size and strain effect have been investigated using XRD analysis. The formation of a single-phase spinel structure has been confirmed by XRD investigation. The crystallitete size (36 – 39) nm, (36 – 43) nm, (46-64) nm, (38-44) nm and corresponding size strain (2.88×10-3-3.13×10-3), (1.98–3.62), (0.52×10-3-1.07×10-3) and (0.58×10-3-1.31×10-3) have been observed with the help of Scherer's formula, modified Scherer's formula, W-H plot and Strain Size Method respectively. High frequency application has been found in initial permeability study. Cole-Cole plot of initial permeability has been observed narrower semicircles with increasing Al content. UV-vis spectroscopy has been used to study optical properties and observed that with increasing Al content reflectance decreases in the (400-700) nm wavelength range. Band gap energy has been found in the range of 1.62 eV to 1.68 eV. Journal of Engineering Science 15(2), 2024, 79-88